Amperometric Sensing of H2O2 using Pt–TiO2/Reduced Graphene Oxide Nanocomposites. Issue 3 (10th September 2013) - Leonardi, Salvatore Gianluca; Aloisio, Davide; Donato, Nicola; Russo, Patrícia A.; Ferro, Marta C.; Pinna, Nicola; Neri, Giovanni
Abstract Nanostructures made of titanium dioxide and/or platinum nanoparticles supported on reduced graphene oxide (RGO) were synthesized by a simple and fast microwave‐assisted route and characterized by X‐ray diffraction (XRD), transmission electron microscopy (TEM), Fourier‐transform infrared (FTIR) and Raman spectroscopies. The composites consist of RGO sheets fully and homogeneously coated with a dense layer of 8 nm TiO2 and/or 2 nm Pt nanoparticles. Screen‐printed flexible sensors based on Pt–TiO2/RGO composites are applied for the amperometric detection of hydrogen peroxide (H2O2). The electrochemical characteristics of Pt/RGO, TiO2/RGO and Pt–TiO2/RGO‐modified screen printed electrodes are investigated and discussed. The developed sensor allows the detection of H2O2, with a linear response from 0 to 20 mM of H2O2 and a sensitivity of 40 μA mM−1 cm−2. The resulting device is also suitable for the analysis of this toxic compound in milk.